Asociación de factores obstétricos y epidemiológicos con la aceptación de la vacunación contra COVID-19 en gestantes atendidas en la Ipress Moronacocha, Iquitos, 2022 - Inga Villacorta, Brizy (2023)
The rejection of vaccination has been recognized as an urgent public health problem, for this reason the present work aims to determine the association of obstetric and epidemiological factors with the acceptance of vaccination against COVID-19 in pregnant women treated at the IPRESS Moronacocha, Iquitos, 2022. An analytical, comparative-representative and cross-sectional study was carried out in 130 patients, to whom the data collection sheet and the Sars-Cov2 Vaccine Perception Measurement Scale were applied. Concluding that the characteristics associated with the rejection of immunization were rural origin (OR: 5,5, p<0,001), primiparous gestation (OR: 5,7, p<0,001), nulliparous (OR: 5,1, p<0,001), pregnant in the second gestational trimester (OR: 4,5, 95% CI: 2,1 – 9,5, p<0,001) and a pre-gestational weight categorized as low weight (OR: 11,7, p<0,001). On the contrary, the characteristics associated with the acceptance of vaccination were pregnant women with higher education (OR: 0,06, p<0,001), multiparous pregnant women (OR: 0,2, p<0,001), pregnant women in the third trimester of pregnancy (OR: 0,2 , p=0,002) and pregnant women with a normal weight (OR: 0,2, p<0,001).